Resilience of Nursing During the Pandemic Covid-19 - Mad Zaini; Komarudin Komarudin; Ginanjar Sasmita Adi (Universitas Muhammadiyah Jember, 2022)
In carrying out their duties, nurses are at the forefront of handling, preventing and caring for Covid-19 patients. Several psychological health problems in nurses emerged as a response to maladaptive coping. This research was conducted to determine the resilience of nurses and the factors that influence it. This quantitative research used a cross-sectional design, carried out on nurses in the Jember Regency area from July-August 2020. The sampling technique used was incidental sampling with a total sample of 117 respondents. From the results of the analysis of the characteristics of respondents based on the place of work that affect the resilience of nurses. Meanwhile, the resilience of most nurses in Jember is at a sufficient level